Local wisdom and Government's role in strengthening the sustainable competitive advantage of creative industries - Mahrinasari, M.S.; Bangsawan, Satria; Sabri, Mohamad Fazli (Elsevier, 2024)
The competitive advantage of the Creative Industry is an important strategy to succeed in a highly competitive global business market. The Indonesian creative industry is a strategic industry characterised by Small and Medium Enterprises (SMEs). However, these enterprises face challenges, such as low entrepreneurial orientation, low digital literation to access the global market, limited capital, lack of digital payment methods, and a focus on conventional marketing activities rather than implementing Entrepreneurial Marketing (EM). The previous research proposed that Entrepreneurial Orientation (EO) and Entrepreneurial Marketing (EM) could increase competitive advantage due to the moderating role of local wisdom culture and the government's role. Therefore, this research aims to analyse the moderating role of local wisdom culture and the government's role in the effect of EO and EM on sustainable competitive advantage development. The quantitative research design employed a self-administered survey distributed to 400 top and middle managers within the superior and priority subsectors of the creative industry. The survey targeted four provinces in Indonesia known for their high contributions to the Gross Domestic Product (GDP >9 %), based on the ‘Purposive Sampling’ method. The results of the SEM analysis, based on 330 useable data points, show that Local Wisdom and Government's Role significantly mediate the relationship between Sustainable Competitive Advantage and Sustainable Business Performance. The research results imply that it is necessary to empower the government's role in providing information technology infrastructure to facilitate the creative industry's access to the global marketplace and encourage the use of digital payment methods for the rapid development of sustainable competitive advantage. Theoretical contributions extend to Dynamic Capability Theory by integrating Resources Advantage Theory and Resources Base View Theory, including the moderating role of Local Wisdom and Government's Role, and examining the relationship of EO and EM with sustainable competitive advantage.